2022
DOI: 10.18800/psico.202202.015
|View full text |Cite
|
Sign up to set email alerts
|

Bullying e cyberbullying: intervenções realizadas no contexto escolar

Abstract: Existem lacunas no contexto latinoamericano no que se refere à divulgação resultados de intervenções antibullying na escola, desta forma, pretendeu-se analisar os resultados de ações para prevenção ou redução da ocorrência de bullying e cyberbullying. Trata-se de uma revisão sistemática da literatura. O levantamento bibliográfico ocorreu nas bases de dados LILACS, PsycINFO, SciELO, SCOPUS e Web of Science. Foram incluídos apenas ensaios clínicos randomizados no ambiente escolar. Um total de nove estudos foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…As reflected in the literature, these behaviours must be intervened upon to avoid “the spiral of violence”, where they not only occur in the adolescent stage but can transcend to the adult stage or other higher educational stages [ 11 ]. The technological context implies that these disruptive behaviours are transferred to virtual spaces [ 12 ]. In fact, some studies show a strong relationship between both types of bullying, noting that many victims/perpetrators of traditional bullying were also victims/perpetrators of cyberbullying [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reflected in the literature, these behaviours must be intervened upon to avoid “the spiral of violence”, where they not only occur in the adolescent stage but can transcend to the adult stage or other higher educational stages [ 11 ]. The technological context implies that these disruptive behaviours are transferred to virtual spaces [ 12 ]. In fact, some studies show a strong relationship between both types of bullying, noting that many victims/perpetrators of traditional bullying were also victims/perpetrators of cyberbullying [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…These disruptive behaviours not only affect students during their compulsory education stage but can also transcend to the university or adult stage [ 11 ]. Moreover, due to technological advances, these problems caused in the school context are transferred to virtual spaces [ 12 ]. In fact, studies have found a strong relationship between the two types of bullying, observing that many victims/perpetrators of traditional bullying were also victims/perpetrators of cyberbullying [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore necessary to implement strategies to prevent the incidence of bullying. Effective strategies over time remain difficult, despite the consistent literature on the subject [ 39 , 40 ]. The existence of awareness and prevention programmes is important.…”
Section: Introductionmentioning
confidence: 99%